Decent work for the digital platform workers. A preliminary survey in Beijing - Y. Xu; D. Liu (Цифровое право, 2021)
This paper discusses the status and implications of the employment relations and working conditions experienced by digital platform workers; the analysis is based on a survey conducted in 2017 on 1 338 workers engaged in work-on-demand via apps (WODVA) from 25 platforms in Beijing, of whom 48.8 % are full-time WODVA workers or take WODVA as their primary job. The survey ﬁnds that nearly a half of the respondents engage in platform work due to a lack of employment opportunities in formal labor markets or their permanent jobs providing insufﬁcient income. The respondents reveal substantial decent work deﬁcits in representation, compensation, job stability, social protection, working time, and health and safety: 1) WODVA workers seldom have any voice in labor dispute settlements and have a very low rate of unionization; 2) about one third of the full-time WODVA workers cannot earn a living wage and 7.6 % of them earn less than the minimum wage level; 3) three quarters of the full-time WODVA workers have no labor contract with the platforms or other employers, nor access to employer-contributed social insurances; 4) overtime work and underemployment coexist among full-time respondents, with nearly 10 % working for fewer than 4 hours per day while nearly 10 % work for more than 11 hours per day; 5) a majority of respondents run a higher risk of occupational health or physical risks, without any protection provided by the platforms or employers. To promote decent work by digital platform workers, the State needs to establish a portable social security system extending to all workers, to facilitate association and collective actions of platform workers either by extending the outreach of traditional unions or fostering new forms of organizations, to leverage digital technology to facilitate platform workers’ organization and information sharing, and even to promote universal basic income and a workers’ cooperative of platforms in the long run.